2018
DOI: 10.22159/ijcpr.2018v10i1.24406
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Mediated Defense Role of Ecliptaalba Herbal Extract Against Ccl4 Inducedtoxic Hepatitis

Abstract: Objective: The present study focuses on the antioxidant mediated the protective effect of a popular medicinal herb Ecliptaalba against CCl4 induced oxidative stress in the liver of rats.Methods: Rats divided into four groups were administered with CCl4 andCCl4 along with methanol extract of leaves of Eclipta herb (200 and 400 mg/kg b. wt) for three weeks. At the end of treatment, rats were anaesthetized and blood samples were collected for serum separation. Biochemical analysis such as alanine aminotransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Through the absence of enough GPx activity or GSH levels, LOP and hydrogen peroxide are not detoxified and perhaps converted by transition metals to hydroxyl radicals and lipid peroxyl radicals. The findings were similar to the results of Kubrak et al [36] and Dahmen-Ben Moussa et al [21] who found decreased GPx, CAT and SOD activities in the rat kidney by Ni cytotoxicty of antioxidant capacity may be coupled with the depletion of GSH and reduced total sulfhydryl contents or with their increased utilization for quenching free radicals and/or their inactivation by excessive Ni oxidation. Furthermore, Ni was reported to trigger nitric oxide (NO) creation [43], which may inhibit both CAT activities by binding to its heme prosthetic group [44] and GPx activity [45].…”
Section: Bouhalit and Kechridsupporting
confidence: 91%
See 1 more Smart Citation
“…Through the absence of enough GPx activity or GSH levels, LOP and hydrogen peroxide are not detoxified and perhaps converted by transition metals to hydroxyl radicals and lipid peroxyl radicals. The findings were similar to the results of Kubrak et al [36] and Dahmen-Ben Moussa et al [21] who found decreased GPx, CAT and SOD activities in the rat kidney by Ni cytotoxicty of antioxidant capacity may be coupled with the depletion of GSH and reduced total sulfhydryl contents or with their increased utilization for quenching free radicals and/or their inactivation by excessive Ni oxidation. Furthermore, Ni was reported to trigger nitric oxide (NO) creation [43], which may inhibit both CAT activities by binding to its heme prosthetic group [44] and GPx activity [45].…”
Section: Bouhalit and Kechridsupporting
confidence: 91%
“…Therefore they can protect the body from oxidative stress and degenerative diseases. GSH is an essential endogenous antioxidant, acts as a cofactor for antioxidant enzymes, directly scavenging ROS and protects cells against free radicals and toxic compounds [36]. The results of nickel exposure were coincide with the findings of Amudha and Pari [2] and Boulila et al [5].…”
Section: Bouhalit and Kechridsupporting
confidence: 79%
“…Secondary metabolites such as terpenoids that gives plants their odors and others metabolites (quinines and tannins) are responsible for plant flavor and some of the herbs and spices used by humans to season food yield useful medicinal compounds. The phenolic and flavonoid compounds are known as powerful chain-breaking antioxidants for their scavenging ability and which is due to their hydroxyl groups [17][18][19][20][21][22][23][24][25]. The phenolic and flavonoids compounds are the most important groups of plant secondary metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…It acts as a scavenger of oxygen free radicals and it replenishes the glutathione stores. It is found to have a good prognosis in patients with yellow phosphorus poisoning when administered early [13,14]. The patient's liver enzymes were highly elevated.…”
Section: Case Reportmentioning
confidence: 99%